Asociación entre riesgo ergonómico y síntomas musculoesqueléticos en odontólogos de la clínica vitadet - Carrera Llano, Mery Johana (2025)
Occupational diseases are an increasingly frequent health problem; among the main causes are working conditions, hazards and various occupational risks to which economically active personnel are exposed worldwide. Among the occupational risks are those of an ergonomic nature, which are associated with the appearance of various musculoskeletal symptoms in numerous professions. The above supports the interest of the research. The present study used a mixed prospective and cross-sectional approach that included 30 dentists who work at the Vitadet Clinic of the Pujilí Canton. The Standardized Nordic Questionnaire and the REBA method were used to collect the data and subsequently the statistical analysis was carried out based on the Chi square statistics or Fisher's Exact Test depending on the case and Cramer's V calculation to establish the existence of association and its magnitude. The results show the existence of musculoskeletal symptoms mainly in the regions of the neck (High), shoulders (Very High) and elbows (High) which have constituted a medium risk for 53% of dentists in need of action while 47% Remaining % are exposed to high risk requiring intervention as soon as possible. The findings allow us to conclude about the association of musculoskeletal symptoms with the ergonomic risks to which dentists are exposed due to the type of activity they perform, showing an association of mostly high magnitude between the variables studied.